Factors affecting indoor radon concentrations in the United Kingdom. - Gunby, J; Darby, S; Miles, J; Green, B; Cox, DR (1993)
Data collected in a nationwide study on natural radiation exposure in UK dwellings (Wrixon et al. 1988) were re-analyzed to investigate the effects of rock type and various building and lifestyle characteristics, taken into account simultaneously, on indoor radon concentrations. A multiplicative model which takes into consideration the outdoor radon concentration is used. Indoor radon concentrations were found to be influenced by type of rock underlying the dwelling, double glazing, house type, floor level of rooms in which measurements were taken, window opening habits in the main bedroom, building materials used in the construction of the walls, floor type, and draught proofing. However, these eight factors together account for only 22% of the variation between dwellings. Estimates of the size of the effect associated with each factor are given.